2017
DOI: 10.1016/j.nima.2016.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Handheld real-time volumetric 3-D gamma-ray imaging

Abstract: This paper presents the concept of real-time fusion of gamma-ray imaging and visual scene data for a hand-held mobile Compton imaging system in 3-D. The ability to obtain and integrate both gamma-ray and scene data from a mobile platform enables improved capabilities in the localization and mapping of radioactive materials. This not only enhances the ability to localize these materials, it provides important contextual information of the scene, which once acquired, can be reviewed and further analyzed subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…A volumetric (3D) Compton imaging (VCI) system to be coupled on a mobile platform was also developed to improve source searching and mapping of unknown environments in nuclear security and safety scenarios [ 188 , 189 ]. This equipment is based on the data fusion of the Compton imager with a Kinect sensor (RGB images) for real-time tracking and 3D scene reconstruction (using SLAM techniques).…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A volumetric (3D) Compton imaging (VCI) system to be coupled on a mobile platform was also developed to improve source searching and mapping of unknown environments in nuclear security and safety scenarios [ 188 , 189 ]. This equipment is based on the data fusion of the Compton imager with a Kinect sensor (RGB images) for real-time tracking and 3D scene reconstruction (using SLAM techniques).…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%
“…This equipment is based on the data fusion of the Compton imager with a Kinect sensor (RGB images) for real-time tracking and 3D scene reconstruction (using SLAM techniques). While Barnowski et al [ 188 ] used a VCI based on HPGe detectors, Haefner et al [ 189 ] implemented a handheld high-efficiency multimode image, based on a two-plane active-mask configuration, which allowed the use of both coded-aperture and Compton imaging modes (total weight 3.6 kg). Haefner et al also reported some important features, like: 3D scene data fusion to improve scene geometry (e.g., RGB data and depth information from Kinect) with gamma-ray image reconstruction from several sources, improvement of spatial resolution and mitigation of the 1/r 2 intensity reduction by bringing the gamma imager closer to the objects, use of RGBD-SLAM algorithm (in which RGB stands for the visual data and D for depth obtained by the Kinect sensor) to simultaneous create 3D model of the environment and to track the detector position and orientation, and list-mode operation using maximum likelihood expectation maximization (ML-EM) method to gamma-ray image reconstruction.…”
Section: Mobile Radiation Detection Systemsmentioning
confidence: 99%
“…Moreover, we have developed a method to three-dimensionally grasp the location of radioactive substances by superimposing images of radioactive substances on a 3-D structural model of the work environment reconstructed using photogrammetry [6]. Haefner and Vetter et al [7,8] reported a method involving superposition of an image of radioactive substances measured using a gamma-ray imager on a 3-D model of the measurement area prepared using Microsoft Kinect or other LRFs to visualize radiation sources on a 3-D real space image. The Microsoft Kinect sensor outputs RGB images and 3-D point cloud data of the scenes.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of both complementary technologies enables unprecedented and “smarter” ways to detect, map, and visualize nuclear radiation fields. Scene-data fusion (SDF) represents the realization of this combination, by integrating “contextual” sensors, such as visual cameras or light detection and ranging (LiDAR), and nuclear radiation detection and imaging instruments [1,2,3,4,5,6]. It enables the mapping and visualization of gamma radiation in 3-D in the context of local scenes while the instrument is being moved through this scene.…”
Section: Introductionmentioning
confidence: 99%